Comparative Study Between Virgin and Agriculture Soil Radon Activity Concentration and Their Radiological Risks - Hiwa Hamad Azeez; Jahfer Majeed Smail; Hemn Muhammad Salh; Habeeb Hanna Mansour; Saddon Taha Ahmad; Hawbash Hamadamin Karim (Polytechnic Journal)
The present study is to compare the radon activity concentration in agricultural and virgin soils from various locations along the Little Zab River (LZR) in the Iraqi Kurdistan region. We conducted 24 measurements of soil samples using long tube techniques equipped with an electric radon detector called RAD7 in our research. The findings revealed that the radon activity concentrations ranged from 37.3 ± 7.52 Bq m-3 to 298.25 ± 50.09 Bq m-3 in virgin soil, and from 33.03 ± 10.85 Bq m-3 to 320.25 ± 34.62 Bq.m-3 in agriculture soil. The annual effective dose was also calculated to be from 0.94 ± 0.19 mSv.y-1 to 8.08 ± 0.87 mSv.y-1 for virgin soil, and from 0.83 ± 0.27 mSv.y-1 to 8.08 ± 0.87 mSv.y-1 for agriculture soil in the Iraqi Kurdistan Region. The field dose rates were measured using the RIIDEye Handheld Radiation Isotope Identifier and found to be within the range 56.8 nSv h-1 to 80.6 nSv h-1. It was observed that Agricultural soil has the highest radiation dose for humans compared to virgin soil.